Inggris dan Perancis pasca Brexit: Sengketa Jersey sebagai Hasil dari Trade and Coooperation Agreement (TCA) - Virajati, Kirana (Andalas Journal of International Studies (AJIS), 2022)
Britain's separation from the European Union led to changes that needed to be re-adjusted by both parties. The European Union-United Kingdom Trade and Cooperation Agreement (TCA) is the result of an adjustment between the UK and the European Union, but does not yet involve the financial sector as one of the crucial sectors. In 2021, there was a blockade by French fishermen of the main Jersey port. As Jersey is a part of the Crown’s Dependency, the foreign affairs of Jersey are also the responsibility of the UK government. This blockade then invited military ships from Britain and France to secure a situation that increased the intensity between the two countries, coupled with a French bluff to block the British process from entering as an external party in the European Union financial sector. This paper discusses the factors that prompted France to issue this response through an economic constructivism approach that looks at the social aspects of the international political economy phenomenon. Based on the results of the discussion, the driving factors for France's attitude were protests by fishermen, perceptions of changes in Jersey maritime activity regulations, as well as uncertainty arising from the post-Brexit situation and regulations arising from TCA.